NiO and Ag@NiO Nanomaterials for Enhanced Photocatalytic and Photoluminescence Studies: Green Synthesis Using Lycopodium Linn. - Basavalingaiah, K. R.; Udayabhanu; Harishkumar, S.; Nagaraju, G.; Chikkahanumantharayappa (Asian Journal of Engineering and Applied Technology, 2019)
NiO and Ag-NiO nano particles were prepared using Lycopodium extract as a fuel via solution combustion synthesis (SCS) at 500 ºC. From the PXRD, FTIR, UV-DRS studies the synthesized NPs were characterized. The morphologies of the prepared NPs were studied by SEM and TEM analysis. The synthesized NPs were tested for photocatalytic and photoluminescence studies. The PXRD data indicated that the synthesized nanoparticles belong to cubic phase structure and space group Fm-3m. The FTIR spectrum of NiO exhibited the absorption bond at 427 cm-1 is associated to Ni-O vibration band. The SEM data revealed that agglomeration was obtained. NiO and Ag-NiO Nps were taken for determine the photocatalytic activity study on methylene blue dye, the results indicated that Ag-NiO NPs exhibited promising photocatalytic activity. This is due to occurrence of Ag particles on the NiO material, which makes the catalyst more sensitive. Furthermore, a photoluminescence study for NiO and Ag-NiO was studied.